Engineering stress solutions for bolted and pressurized steel structures. (February 2015) - Aleksandrova, Nelli
Abstract: Two geometrical models of bolted connections and pressurized containers are suggested. A unified analytical procedure for stresses is developed based on the Huber–Mises–Hencky yield criterion, elastic–perfectly plastic material behavior and plane stress assumption. To determine the minimum distance between centers of fasteners in bolted connections the limit load-carrying capacity criterion is proposed. The results obtained agree well with AISC specifications and on the safe side. For pressurized containers it is shown that stress distributions depend on Poisson's ratio which should be taken into account in a stability analysis since these structures are mostly vulnerable to the local loss of geometric stability.